What can other animals tell us about human social cognition? An evolutionary perspective on reflective and reflexive processing - Hecht, Erin E.; Patterson, Richard; Barbey, Aron K. (Frontiers in Human Neuroscience, 2012)
Human neuroscience has seen a recent boom in studies on reflective, controlled, explicit social cognitive functions like imitation, perspective‐taking, and empathy. The relationship of these higher‐level functions to lower‐level, reflexive, automatic, implicit functions is an area of current research. As the field continues to address this relationship, we suggest that an evolutionary, comparative approach will be useful, even essential. There is a large body of research on reflexive, automatic, implicit processes in animals. A growing perspective sees social cognitive processes as phylogenically continuous, making findings in other species relevant for understanding our own. One of these phylogenically continuous processes appears to be self‐other matching or simulation. Mice are more sensitive to pain after watching other mice experience pain; geese experience heart rate increases when seeing their mate in conflict; and infant macaques, chimpanzees, and humans automatically mimic adult facial expressions. In this article, we review findings in different species that illustrate how such reflexive processes are related to (“higher order”) reflexive processes, such as cognitive empathy, theory of mind, and learning by imitation. We do so in the context of self‐other matching in three different domains – in the motor domain (somatomotor movements), in the perceptual domain (eye movements and cognition about visual perception), and in the autonomic/emotional domain. We also review research on the developmental origin of these processes and their neural bases across species. We highlight gaps in existing knowledge and point out some questions for future research. We conclude that our understanding of the psychological and neural mechanisms of self‐other mapping and other functions in our own species can be informed by considering the layered complexity these functions in other species.